Increased discrimination between benign prostatic hyperplasia and prostate cancer with equimolar total prostate specific antigen measurement - Onur, R; Ilhan, N; Orhan, I; Ilhan, N (Springer-Verlag, 2003)
Although prostate specific antigen (PSA) is widely used in the discrimination of benign prostatic hyperplasia (BPH) and prostate cancer, its diagnostic value is controversial due to an appreciable false positive rate. In the present study, we compared a recently introduced assay method, equimolar PSA measurement, to non-equimolar PSA measurement and also determined the diagnostic value of percent free PSA with changing total PSA (tPSA) measurements. Between April 1999 and December 2001, the sera of 61 patients with BPH and 41 with prostate cancer were examined. Total PSA and free PSA was determined using the Immulite 2000 assay system, whereas equimolar tPSA measurement was performed using Bayer PSA Q for the Chiron ACS 180 system. Comparative analysis of the two different assays revealed better diagnostic sensitivity and specificity values for equimolar tPSA measurement, which in turn would have led to 10% of the patients avoiding an unnecessary biopsy. Additionally, percent free PSA with the changing denominator of tPSA assays showed that the free PSA/equimolar tPSA ratio was the best tumor marker among the studied forms of PSA. It was concluded that equimolar tPSA measurement using recombinant Fab fragments is superior to the classical measurements with monoclonal antibodies, and that the use of percent free PSA with the equimolarly measured tPSA has better sensitivity and specificity in the discrimination of benign and malignant diseases of the prostate.
Keywords: prostate specific antigen; equimolar measurement; benign prostatic hyperplasia; prostate cancer